The Values of Jaranan Pogogan Art Teguh Rahayu at Sugihwaras Village, Prambon Sub-District, Nganjuk Regency. - Bekti, Wahyu Prasetyo; Sunarto, Sunarto; Utomo, Udi (Universitas Negeri Semarang, 2020)
Jaranan Pogogan art Teguh Rahayu have its own uniqueness. The uniqueness lies in the presentation performed on stage, and is presented by two male dancers who dress up like a pretty woman. A dancer is as a Sasra and another dancer is as Pogog. The purpose of this research is to analyse the values of the art performance of Jaranan Pogogan Teguh Rahayu. This study used a descriptive qualitative approach with a case study model at the art performance of Jaranan Pogogan Teguh Rahayu. This research was conducted in Sugihwaras village, Prambon Sub-district, Nganjuk Regency. The data in this research is classified as two, namely primary data and secondary data. The data collection techniques in this study are field observations, interviews, documents, and library studies. The triangulation is used as the process in the validity of the data of this study. Technique of analysis data used data reduction, data presentation and conclusion and verification. The results showed that there are four values contained in the Pogogan Teguh Rahayu Arts Museum, they are as follows; the value of deity, the value of goodness, the value of righteousness, and the value of beauty. This analysis uses some value on the Pogogan Teguh Rahayu Art which the values reflected in daily activities.